ISU-ISU PENGELOLAAN LINGKUNGAN PADA HOTEL BERBINTANG DI BALI - Pramono, Jaya (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016)
Aim of this studyis to identify environmental management issues at starred hotels in Bali. Respondent of this study was 126 hotel manager. The data obtained through questionnaire which was analyzed by descriptive statistic. The findings show that environmental management issues take an important place to the hotel management and emerge as bases for hotel manager of starred hotels in Bali for carrrying out environmental management. Out of seven issues analyzed in this study, three of them emerge as important issues i.e. pressure from travel agent, pressure from customer and tourist, and cimate change. There is a significant difference among one, two, and three starred hotels and four and five starred hotels related to the significance of those issues. For manager of one, two, and three starred hotels, those issues are in “important” category, whereas for four and five starred hotels, they are in “very important” categories which push them to do management of environment.
Keywords: environmental management issue, starred hotel, travel agent, climate change